2014
DOI: 10.1111/asj.12161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different levels of protein supplementary diet on gene expressions related to intramuscular deposition in early‐weaned yaks

Abstract: This study was conducted to estimate different levels of protein supplementary diet on gene expressions related to intramuscular deposition in early-weaned yaks. Results showed that supplementary dietary protein significantly increased final weight, average daily gain (ADG), intramuscular fat (IMF), serum free fatty acid (FFA), total triglycerides, total cholesterol (Ch), low-density lipoprotein cholesterol (LDL) and high-density lipoprotein cholesterol (HDL) content. There was a quadratic response of ADG, IMF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…It has been shown that the content of intramuscular fat can be radically increased by low lysine dietary supplementation in finishing gilts (Katsumata et al, 2005). Furthermore, restricted protein content (Teye et al, 2006), manipulation of dietary energy and protein (Zhang et al, 2014) and conjugated linoleic acid (Zhong et al, 2011) were found to have beneficial effects for intramuscular fat deposition in finishing as well as young porcine. At the metabolic level, fat deposition is a complex and coordinated process and as a result of dynamic balance among fatty acid transportation, lipogenesis and lipolysis in tissue (Jurie et al, 2007).…”
Section: Fat Depositionmentioning
confidence: 99%
“…It has been shown that the content of intramuscular fat can be radically increased by low lysine dietary supplementation in finishing gilts (Katsumata et al, 2005). Furthermore, restricted protein content (Teye et al, 2006), manipulation of dietary energy and protein (Zhang et al, 2014) and conjugated linoleic acid (Zhong et al, 2011) were found to have beneficial effects for intramuscular fat deposition in finishing as well as young porcine. At the metabolic level, fat deposition is a complex and coordinated process and as a result of dynamic balance among fatty acid transportation, lipogenesis and lipolysis in tissue (Jurie et al, 2007).…”
Section: Fat Depositionmentioning
confidence: 99%
“…; Zhang et al . ). CLAs consist of positional and geometric isomers of linoleic acid, which contain conjugated double‐bond systems.…”
Section: Introductionmentioning
confidence: 97%
“…About 15 million or more than 90% of the world’s total yak population are currently herded in Chinese territories, which are important for Tibetan herders in providing milk, meat and transport (Zhang et al, 2014). Yak have to survive during inadequate feed supply in the long cold season (October to May) due to herbage deficiency under traditional pure grazing farming system, which is a centuries old grassland yak production cycle, where the yak is expected to satiate in summer, fatten in fall, become thin in winter, and die in spring (Xue et al, 2005).…”
Section: Introductionmentioning
confidence: 99%